Cutaneous manifestations associated with antiphospholipid antibodies in patients with suspected primary antiphospholipid syndrome: a case-control study. Issue 3 (March 1993) - Naldi, L; Locati, F; Marchesi, L; Cortelazzo, S; Finazzi, G; Galli, M; Brevi, A; Cainelli, T; Barbui, T
Abstract : OBJECTIVE: To study the association of a variety of dermatological manifestations related to vascular abnormalities with antiphospholipid antibodies in patients with suspected primary antiphospholipid syndrome. METHOD: Case-control study. Consecutive patients referred to the coagulation and haemostasis service of a general hospital for the first determination of antiphospholipid antibodies (lupus anticoagulant and anticardiolipin antibodies) and newly diagnosed disorders (for example, thrombocytopenia, thrombotic disorders, and unexplained repeated abortions) were selected. Patients were examined by two dermatologists according to predefined criteria, and information about general characteristics and relevant dermatological and medical histories were collected using an ad hoc questionnaire. The study was limited to patients without evidence of systemic lupus erythematosus. A total of 35 patients was examined; 13 subjects were positive for lupus anticoagulant or anticardiolipin antibodies, or both (cases), and 22 were negative (controls). RESULTS: Moderate to severe livedo reticularis and acrocyanosis were significantly associated with antiphospholipid antibodies, with relative risks of 13.1 (95% confidence interval 1.1 to 149.0) and 8.6 (95% confidence interval 1.1 to 65.1). Capillaritis was also associated with the antibodies. Histories of Raynaud's phenomenon and superficial thrombophlebitis were more common in cases than controls. CONCLUSIONS: This study provides quantitative evidence of the association of antiphospholipid antibodies with several cutaneous diseases in which vascular abnormalities seem to play a major part. The study suggests that these manifestations might appear early in the development of the antiphospholipid syndrome.